Papain-like cysteine proteases are required for the regulation of photosynthetic gene expression and acclimation to high light stress - Alomrani, Sarah (Journal of experimental botany, 2021)
© The Author(s) 2021. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.